Allium peikingense (Amaryllidaceae, Allioideae), a new species from Beijing, China - Cheng, Rui-Yu; Yang, Jing-Tian; Tan, Jin-Bo; Zhou, Song-Dong; He, Xing-Jin; Xie, Deng-Feng (Phytotaxa, 2025)
Allium peikingense, a new species from the mountainous area west of Beijing, China, is described and illustrated herein. Morphological and phylogenetic evidence from 40 sampled populations consistently supports its placement within subgenus Caloscordum of the genus Allium. Although A. peikingense is very similar to A. neriniflorum and A. tubiflorum, it can be distinguished by its white tepals with relatively blunt apices, broader hollow semi-cylindrical leaves, four mature seeds per ovary, and a tetraploid chromosome number of 2n = 4x = 32. Phylogenetic analyses based on nuclear ribosomal internal transcribed spacer (ITS) sequences and a dataset of 45 plastid sequences further demonstrate that all individuals of A. peikingense cluster into a distinct clade closely related to other species in the subg. Caloscordum, including A. neriniflorum, A. tubiflorum, and A. inutile. Detailed descriptions of morphological traits and habitat differences are also provided.